2015
DOI: 10.1155/2015/703574
|View full text |Cite
|
Sign up to set email alerts
|

Slip Effects on Peristaltic Transport of a Particle-Fluid Suspension in a Planar Channel

Abstract: Peristaltic pumping induced by a sinusoidal traveling wave in the walls of a two-dimensional channel filled with a viscous incompressible fluid mixed with rigid spherical particles is investigated theoretically taking the slip effect on the wall into account. A perturbation solution is obtained which satisfies the momentum equations for the case in which amplitude ratio (wave amplitude/channel half width) is small. The analysis has been carried out by duly accounting for the nonlinear convective acceleration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…4d, however impedes pressure gradient very strongly since it is associated with deceleration in the fluid phase. The Newtonian case (1 =0) achieves the greatest axial pressure gradient which is consistent with other studies-see for example Shahidian et al [49]. With increasing particle suspension ( Fig.…”
Section: Numerical Results and Interpretationsupporting
confidence: 92%
See 1 more Smart Citation
“…4d, however impedes pressure gradient very strongly since it is associated with deceleration in the fluid phase. The Newtonian case (1 =0) achieves the greatest axial pressure gradient which is consistent with other studies-see for example Shahidian et al [49]. With increasing particle suspension ( Fig.…”
Section: Numerical Results and Interpretationsupporting
confidence: 92%
“…Further analyses have been communicated by Medhavi and Singh [48], Kamel et al . [49], Bahiraei [50,51,52], Bahiraei et al [53,54,55] the latter also addressing multi-phase flows.…”
Section: U Sir Is a DI Git Al C Oll E C Tio N Of T H E R E S E A R C mentioning
confidence: 99%
“…into the equation 30 and the boundary conditions 45 and 47 into the equation 31, then the second order equations of the fluid and the particle can be written as: 2 2 2 1 1 2 3 1 2 1 1 2 2 2 2 2 2 2 1 2 1 Equations 64, 65 (with neglecting the effect of magnetic field on the flow behavior)represent the same formula reached by Eldesoky [25].…”
Section: Mathematical Formulationmentioning
confidence: 95%
“…Some more studies on the said topic can be found from the list of refs. [29][30][31] and several therein.…”
Section: Introductionmentioning
confidence: 98%